Does mandatory turnout affect the quality of the political representation process? : a cross-national study on the “second-order effects” of the compulsory voting law. - Natália Nunes Aguiar (2023)
This dissertation investigates the relationship between compulsory voting (CV) and the quality of the political representation process. I discuss the notion of quality regarding various approaches to the political representation process and seek to answer the question: does mandatory voting hinder the quality of the political representation process? To that end, I offer a structured analysis of the literature on the second-order effects of CV and explore how the existing research relates to the distinct aspects of the political representation process. I also identify the theoretical background of different approaches to the idea of quality in the process of political representation and offer an empirical assessment of it: the accountability model as measured by economic voting. I conduct two sets of analyses to test the hypotheses: one based on an aggregate-level database that I constructed and the other based on individual-level data from the Comparative Study of Electoral Systems. The data do not support the general hypothesis: there is no evidence that CV hinders the accountability process. Whether at the macro or micro level, assessed objectively or subjectively, economic issues relate to the process of political representation in the same way under compulsory and voluntary voting systems.